The dynamics of phenotypic change and the shrinking sheep of St. Kilda. - Ozgul, A; Tuljapurkar, S; Benton, T; Pemberton, J; Clutton-Brock, T; Coulson, T (2009)
Environmental change, including climate change, can cause rapid phenotypic change via both ecological and evolutionary processes. Because ecological and evolutionary dynamics are intimately linked, a major challenge is to identify their relative roles. We exactly decomposed the change in mean body weight in a free-living population of Soay sheep into all the processes that contribute to change. Ecological processes contribute most, with selection--the underpinning of adaptive evolution--explaining little of the observed phenotypic trend. Our results enable us to explain why selection has so little effect even though weight is heritable, and why environmental change has caused a decline in the body size of Soay sheep.